An Analysis of Figurative Language in Sabrina Carpenter’s Song Album “Short N’ Sweet” - Gea, Mira Kristiyanti; Pasaribu, Tiara Kristina; Sinambela, Erika (JALL (Journal of Applied Linguistics and Literacy), 2025)
The study is very important because when listening to songs, most people only focus on the music rather than the lyrics without knowing the meaning of the song. This study aims to find out the types of figurative language in “Short n Sweet” song album by Sabrina Carpenter and  how is the figurative language realized in the song album. This research used mix-method research namely quantitative and qualitative. This study used Perrine (1992) theory which classified figurative language into 12 types. However, this research only focuses into 6 types of figurative language with the research results of 97 data. There are Metaphor (16), Simile (14), Personification (9), Symbol (19), Hyperbole (23), and Irony (16). The realization is that there are six types of  figurative language, namely metaphors (comparing two different ideas, namely intelligence with sharpest tools and describing a partner with bee). Simile (make a direct comparison using the term "like"). Personification (inanimate objects namely fan and car are given human characteristics or talents). Symbol (use elements of numbers and drink brands with meanings that are different from their literal meanings). Hyperbole (use clearly exaggerated statements to emphasize certain feelings and situations). Irony (there is a mismatch between what is said or expected and the truth or deepest feelings behind the statement). This study is very important for english department and literature students, teacher, lecturer, and other researchers because it will teach them how to evaluate and analyze figurative language both in songs and in other media.